2007
DOI: 10.1007/s11165-006-9029-2
|View full text |Cite
|
Sign up to set email alerts
|

Purposely Teaching for the Promotion of Higher-order Thinking Skills: A Case of Critical Thinking

Abstract: This longitudinal case-study aimed at examining whether purposely teaching for the promotion of higher order thinking skills enhances students' critical thinking (CT), within the framework of science education. Within a pre-, post-, and post-post experimental design, high school students, were divided into three research groups. The experimental group (n=57) consisted of science students who were exposed to teaching strategies designed for enhancing higher order thinking skills. Two other groups: science (n=41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
236
0
38

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 450 publications
(320 citation statements)
references
References 32 publications
10
236
0
38
Order By: Relevance
“…In the classroom, abilities and skills that include the use of HOTS are complex thinking that goes beyond basic recall of fact, such as evaluation and invention, enabling students to retain information and to apply problem-solving solution to real-world problems. Barak, David, and Uri (2007), stated that HOTS is composed of three components: critical, systems, and creative thinking, while according to Wang and Wang (2011), there are three main components in HOTS, i.e. critical thinking skills, thinking design and systems thinking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the classroom, abilities and skills that include the use of HOTS are complex thinking that goes beyond basic recall of fact, such as evaluation and invention, enabling students to retain information and to apply problem-solving solution to real-world problems. Barak, David, and Uri (2007), stated that HOTS is composed of three components: critical, systems, and creative thinking, while according to Wang and Wang (2011), there are three main components in HOTS, i.e. critical thinking skills, thinking design and systems thinking.…”
Section: Introductionmentioning
confidence: 99%
“…critical thinking skills, thinking design and systems thinking. Based on these two statements, then the creative thinking skills proposed by Barak et al (2007) similar to design thinking skills proposed by Wang and Wang (2011). Thus there are three components in HOTS, namely: (1) critical thinking skills, (2) creative thinking skills, and (3) systems thinking skills.…”
Section: Introductionmentioning
confidence: 99%
“…When life goes, a supposedly able to make rational decisions based on critical thinking instead of accepting the authority. Therefore, students must be prepared to question the axioms, raises doubts, investigate the situation, and the investigation of alternative, in the context of two schools (colleges) and everyday life [14]. Critical thinking skills is an ability that is essential for life, work and function effectively in all other aspects of life [20] [21] [19] [11] [28] [6].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou, Huang, and Tian (2013), CTS are such an integral part of modern education that one cannot be separated from the other. CTS are an indispensable instrument in modern society, enables students to effectively face the challenges in building new ideas, making correct selections, and understanding the world around them (Miri, David, & Uri, 2007;Shakirova, 2007;Snyder & Snyder, 2008;ZOLLER, 2001;Zoller & Pushkin, 2007). Furthermore, Snyder and Snyder (2008) posits that, CTS are learned skills and a product of education, training and practice that must be developed, practiced; and constantly integrated into the curriculum in order to engage students in active learning.…”
mentioning
confidence: 99%
“…To overcome these challenges, Miri et al (2007); and Zoller et al (2000) suggested that, CTS should be integrated into the students' training in order to serve as a catalyst toward the analysis of unfamiliar objectives); and assessment and evaluation (selecting and implementing the methods that will be used to determine whether and how well the objectives have been achieved and interpreting the results) (Felder & Brent, 2003). These domains are illustrated in figure 1.…”
mentioning
confidence: 99%